General Decay for a Coupled System of Viscoelastic Wave Equation of Infinite Memory with Acoustic Boundary Conditions - Abdelaziz Limam (Université de M'sila, 2022)
coupled system of viscoelastic wave equation of infinite memory is considered. Our system is coupled with the acoustic boundary conditions. Under a very general assumption on the relaxation function, we establish a uniform decay rate. This work substantially improves the earlier results in cases of acoustic boundary conditions. Index Terms—viscoelastic damping, convex functions, general decay